2020
DOI: 10.1002/jmri.27345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Aortic Wall Thickness, Stiffness and Flow Reversal in Patients With Cryptogenic Stroke: A 4D Flow MRI Study

Abstract: Background Stroke etiology is undetermined in approximately one‐sixth to one‐third of patients. The presence of aortic flow reversal and plaques in the descending aorta (DAo) has been identified as a potential retrograde embolic mechanism. Purpose To assess the relationships between aortic stiffness, wall thickness, and flow reversal in patients with cryptogenic stroke and healthy controls. Study Type Prospective. Population Twenty one patients with cryptogenic stroke and proven DAo plaques (69 ± 9 years, 43% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The segmentation results were used to mask the 4D-flow velocity field and perform volumetric hemodynamic analyses. Parametric hemodynamic mapping of FF, RF, flow stasis, and KE was performed using an in-house MATLAB program according to a recently reported workflow ( Shen et al, 2018 ; Jarvis et al, 2020 ; Jarvis et al, 2021 ). Briefly, 4D-flow data were interpolated to isotropic voxels (1 mm × 1 mm × 1 mm) using cubic spline interpolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmentation results were used to mask the 4D-flow velocity field and perform volumetric hemodynamic analyses. Parametric hemodynamic mapping of FF, RF, flow stasis, and KE was performed using an in-house MATLAB program according to a recently reported workflow ( Shen et al, 2018 ; Jarvis et al, 2020 ; Jarvis et al, 2021 ). Briefly, 4D-flow data were interpolated to isotropic voxels (1 mm × 1 mm × 1 mm) using cubic spline interpolation.…”
Section: Methodsmentioning
confidence: 99%
“…However, most of these flow-based parameters are derived using 2D plane-based approaches ( Stalder et al, 2008 ), which have been shown to underestimate true values ( Shen et al, 2018 ), and it does not take advantage of the 3D nature of 4D-flow MRI. Shen et al( Shen et al, 2018 ) and Jarvis et al ( Jarvis et al, 2020 ; Jarvis et al, 2021 ) recently introduced 3D voxel-by-voxel methods that provide 4D-flow derived parametric mapping of FF, RF, kinetic energy (KE) and stasis in the thoracic aorta. In this study, we applied 4D-flow derived parametric mapping to: ( Siu and Silversides, 2010 ): evaluate differences in 3D-derived aortic parametric voxel-by-voxel hemodynamic markers between BAV patients and healthy controls, ( Sievers and Schmidtke, 2007 ), explore associations between these markers and a structural marker of aortopathy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…5 22 Age has been shown to be associated with differences in flow and vessel wall parameters. 23 Although using age-and sex-matched control subjects would be ideal, this was limited by the invasive nature of DSA. Thus, it might be better to investigate and quantify hemodynamic parameters in patients with carotid vessel disease using non-invasive methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies using transesophageal echocardiography or 4D-MRI showed aortic flow reversal without aortic regurgitation [1,3,4]. Evidence has indicated that arterial stiffness and wall thickness, which are associated with aging and atherosclerosis, can lead to flow reversal due to a mismatch between peripheral and central arterial stiffness [3,4]. Typically, retrograde blood flow originates in the first 20-30 mm of the proximal DAo and can reach all brain-supplying arteries [2].…”
Section: Discussionmentioning
confidence: 99%